An Invention of Smart Glove to Help the Elderly Patients - Bobby , J. Sofia; Elona , J. Jane; Bismi , J. H.; Kumar , M. Dinesh (Advances and Challenges in Science and Technology Vol. 3, 2023)
Aging is characterized as the progressive decline of physiological capabilities required for life and reproduction over time. Everyone in the world should take care of old patients and treat them the way they should be handled. Most older people are encountering health problems as they age and are being placed in homes and orphanages. Elders are unable to visit doctors on a regular basis to assess their health state. This article proposes a remedy for the elderly patients in the area by aiding them and encouraging them to be unafraid. The suggested system takes use of many characteristics such as GPS and GSM modules, a pulse oximeter, an accelerometer, a touch sensor, and Bluetooth that communicate with the Arduino. The suggested smart glove is used to assess temperature, detect falls, and monitor pulse rate in elderly individuals who are experiencing health problems. In this context, for client health care, the proposed system is based on supported mobile health technology and employs a smart glove to authorize caregivers or physicians to line up as well as examine the history of the patient's physiological data during his or her absence from the clinical center or home. These statistics will assist them in caring for older patients during challenging times for their survival. Furthermore, this smart glove is quite important for women's protection in order to keep them protected from harm.